Phytochemical Profiling of Nutmeg (Myristica fragrans Houtt.) Seeds: A Qualitative Screening Approach - Bahri, Syamsul; Merta, I Wayan (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Nutmeg is a warm, aromatic spice derived from the seed of the Myristica fragrans evergreen tree, native to Indonesia's Banda Islands. It features a rich, slightly sweet flavor with hints of clove and pepper, commonly used in both baked goods and savory dishes. This study aims to profile secondary metabolites of ethanolic extracts of nutmeg seeds. Dried seeds of the nutmeg were extracted using 96% ethanol, and the resulting extract was subjected to standard phytochemical screening tests to identify major secondary metabolites. The results revealed a strong presence of alkaloids, flavonoids, and terpenoids, indicating that these compounds are dominant constituents in the ethanolic extract. In addition, tannins and phenolic compounds were detected in smaller amounts. Conversely, saponins and steroids were undetectable in the extract. These findings indicate that ethanol is an effective solvent for extracting alkaloids, flavonoids, and terpenoids from the seeds of the nutmeg, while its efficiency for terpenoids and saponins may be limited. The presence of these secondary metabolites supports the potential biological activity of the seeds of the nutmeg and provides a scientific basis for their further pharmacological and biological activity studies.